Efforts to Improve Students' Creative Intelligence through Basic Questioning Skills in Indonesian Language Subjects at MI Darussalam Bengkulu City - Asiyah, Asiyah; Topano, Adrian (Yayasan Darusssalam Bengkulu, 2020)
The results showed that the learning implementation process in MI Darussalam in terms of the approach, model, method, strategy carried out by the teacher turned out to be running well, through learning activities including planning, approaches, models, methods, strategies, to the final stage. The teacher delivers in accordance with the teacher's Rpp and is supported by the teacher manual and student books. The application of basic questioning skills in learning has been applied in MI Darussalam even though it is optimal and has not mastered basic questioning skills but basic questioning skills are applied in the hope that it can improve student knowledge and learning outcomes. Efforts to improve students' creative intelligence through basic questioning skills are of several kinds. what the teacher does such as inviting students to learn while playing, inviting students to ask questions about what they do not know, giving questions to students from before the opening to the end of the lesson, giving awards in the form of gifts to students who dare to answer or give questions during learning, how to This can increase students' creative intelligence and be able to improve student learning outcomes and increase the curiosity of students.